Walking Memories, Future Dreams: Exploring Design through Cartographies, Speculation and AI - Bruscato Portella, Grazielle (Sage Journals, 2024)
This paper summarizes a design practice (“Take the Memory Out for a Future Walk”) conducted with undergraduate students in a park in Barcelona. Through walking, sensory mapping, artificial intelligence exploration, and prototyping, participants explored the interplay between embodied experiences, memory, future speculation, and design intervention. Walking the park fostered sensory engagement, shaping students' understanding of the site and its history. This informed the development of projects addressing environmental concerns and promoting sustainable practices through reimagined spaces or objects. Students employed AI tools to generate ideas where they envisioned alternative futures and challenged existing norms. This process encouraged non-canonical reflection, urging students to move beyond conformistic approaches while fostering future-oriented critical thinking. The practice yielded valuable insights for design education. Firstly, it showed why the integrating walking and sensory mapping into design processes can challenge space determinism. In addition, it contributed to the potential of speculative design and future studies to foster alternative imagination and address pressing issues like climate change, promoting planetary awareness. Further iterations could benefit from expanding on-site exploration and incorporating material limitations to deepen student engagement with the natural surroundings, community and project sustainability.
Keywords: 58 Pedagogía::5801 Teoría y métodos educativos::5801.07 Métodos pedagógicos; ODS 4 - Educación de calidad; Speculative Design; Future Studies; Artificial Intelligence; Design Pedagogical Methodology; Sustainability; Cartography.